2003
DOI: 10.1046/j.1365-246x.2003.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-seismic relaxation and earthquake triggering in the southern Adriatic region

Abstract: SUMMARY An attempt at quantifying post‐seismic relaxation triggered by decoupling earthquakes along the eastern thrusting border of the Adriatic plate (southern Dinarides) is carried out by finite element modelling, with a model constituted by an elastic lithosphere riding on a viscous asthenosphere. In particular, it is investigated the possibility that the above phenomenon is responsible for the fact that in the last two centuries most major earthquakes in the southern Dinarides (MS > 6) have been followed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 76 publications
1
50
0
Order By: Relevance
“…For example, a Maxwell time t = h/G, with t = 50 days and a shear modulus for lower continental crust of G = 40 GPa, leads to a dynamic viscosity h of around 1 Â 10 17 Pa s for the lower crust. This is 1 -2 orders of magnitude smaller than expected for the lithosphere [Pollitz and Bürgmann, 1998;Viti et al, 2003]. That is, the timescale of our problem (50 days) is 1 or 2 orders of magnitude too short to be related to viscous behavior of a relatively cold, lower continental crust.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, a Maxwell time t = h/G, with t = 50 days and a shear modulus for lower continental crust of G = 40 GPa, leads to a dynamic viscosity h of around 1 Â 10 17 Pa s for the lower crust. This is 1 -2 orders of magnitude smaller than expected for the lithosphere [Pollitz and Bürgmann, 1998;Viti et al, 2003]. That is, the timescale of our problem (50 days) is 1 or 2 orders of magnitude too short to be related to viscous behavior of a relatively cold, lower continental crust.…”
Section: Discussionmentioning
confidence: 58%
“…[31] Postseismic viscous relaxation processes [Pollitz and Bürgmann, 1998;Viti et al, 2003] can be excluded because of the short timescale of the observation. For example, a Maxwell time t = h/G, with t = 50 days and a shear modulus for lower continental crust of G = 40 GPa, leads to a dynamic viscosity h of around 1 Â 10 17 Pa s for the lower crust.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reinforced by analogy with the eruptive activity of Vesuvius, although the physical nature of the relationship is not fully clarified. The synchronous behavior of large areas or areas that are very distant from each other has been observed for earthquakes in Italy (Viti et al 2003;Mantovani et al 2010;Bragato 2014) and elsewhere (Bath 1984a, b;Tsapanos and Liritzis 1992;Liritzis et al 1995;Bragato and Sugan 2014), as well as for volcanoes (Marzocchi et al 2004). The explanatory theories for the phenomenon are of different nature.…”
Section: Discussionmentioning
confidence: 80%
“…Some models rely on the earthquake-to-earthquake interaction through different mechanisms of stress transfer (Freed 2005). Among them, those based on post-seismic viscoelastic relaxation explain triggering at distances of the order of 100 of kilometers with delays of some years (Viti et al 2003). Another class of models involves transient crustal deformation at the level of entire plates or portions of plates (Kasahara 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the SHARE European Earthquake Catalog (Stucchi et al 2012) represents an attempt to revise and integrate the various catalogs adopting common standards, but the quality of the overall common catalog is far from being comparable with that of the Italian one (especially for what concerns the minimum magnitude of completeness). Nonetheless, a few studies (Mantovani and Albarello 1997;Viti et al 2003;Mantovani et al 2010) have found some degree of synchronization (although with no periodicity) between the strong earthquakes occurring on the two sides of the Adriatic Sea, in correspondence with the borders of the Adriatic microplate (Southern Apennines on west and Southern Dinarides-Albanides on east).…”
Section: Discussionmentioning
confidence: 99%